Identifikasi Cemaran Mikroba Pada Jamu Tradisional Yang Dijual Di Pasar Andir Kota Bandung - Ni'matul Murtafi'ah; Purwaeni Purwaeni; Deti Kurnia (Jurnal Kesehatan Rajawali, 2023)
Pasar Andir, Bandung City, is one of the markets where herbal medicine sellers carry it. The use of water to wash used glasses that look cloudy. This is a source of microbial contamination. This research was to determine the presence of bacterial and mold/yeast contamination as well as the identification of gram staining and fungal staining. This study uses a descriptive observation method. The results of the calculation of Total Plate Number and Yeast Mold Number compared to KBPOM No. 12 of 2014 colonies â‰¤106 Colonies/g, while for Mold and Yeast: â‰¤104 Colonies/g. Testing the Plate Count The total bacteria did not exceed the contamination limit, while the calculation of the Fungal Number of the JGK, JGT samples exceeded the contamination limit. Results of gram staining of JGK gram-negative bacilli, JGJ and JGK gram-positive cocci. The result of the staining of the JGK sample was yeast, while the JGJ and JGT samples were mold.